Na3Y3(BO3)4: a new noncentrosymmetric borate with an open-framework structure. Issue 17 (7th April 2016) - Shan, Faxian; Kang, Lei; Zhang, Guochun; Yao, Jiyong; Lin, Zheshuai; Xia, Mingjun; Zhang, Xinyuan; Fu, Ying; Wu, Yicheng
Abstract : A new noncentrosymmetric borate Na3 Y3 (BO3 )4 was synthesized. It features a zeolite-type framework, which is extremely rare in borates. Abstract : A new noncentrosymmetric borate, Na3 Y3 (BO3 )4, was grown in the Na2 O–B2 O3 –NaF flux system. Its open-framework structure features a large hexagonal tunnel (5.92 Å in diameter), which is extremely rare in borates. First-principles calculations on its kinetic stability and optical properties were performed.